2020
DOI: 10.1186/s40529-020-00301-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of circadian clock and light on melatonin concentration in Hypericum perforatum L. (St. John’s Wort)

Abstract: Background Melatonin acts as a signaling hormone and entraining agent in many organisms. We studied the spatiotemporal regulation and influence of light (photoperiods, intensities, and spectral qualities) on melatonin concentration in the medicinal herb Hypericum perforatum L. Furthermore, melatonin concentrations in the leaves of eight species of the Hypericum genus were compared and analyzed using high-performance liquid chromatography. Results Melatonin concentration was found to be the highest in its flo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
(79 reference statements)
0
9
0
3
Order By: Relevance
“…Furthermore, melatonin plays a key role in circadian rhythms and in seasonal photoperiodic regulation in both animal and plant systems. 34,35 Almost all stages of plant development are controlled by the circadian clockfor example, germination, growth, and the onset of flowering. Other processes, such as stomatal opening, hormone regulation, signaling, and responses to biotic and abiotic attacks, are also modulated by the circadian clock.…”
Section: Natural Sources Of Melatonin and Health Benefitsmentioning
confidence: 99%
“…Furthermore, melatonin plays a key role in circadian rhythms and in seasonal photoperiodic regulation in both animal and plant systems. 34,35 Almost all stages of plant development are controlled by the circadian clockfor example, germination, growth, and the onset of flowering. Other processes, such as stomatal opening, hormone regulation, signaling, and responses to biotic and abiotic attacks, are also modulated by the circadian clock.…”
Section: Natural Sources Of Melatonin and Health Benefitsmentioning
confidence: 99%
“…Melatonin represents another stress-responsive metabolite involved in antioxidant defense in several Hypericum representatives, e.g., H. perforatum, or H. kouytchense (Murch and Saxena, 2006;Nguyen et al, 2018;Chung and Deng, 2020;Khan et al, 2020). According to Zhou et al (2021), the overexpression of HpSNAT1 gene coding for serotonin Nacetyltransferase (SNAT), the key enzyme involved in melatonin biosynthesis resulted in more than 4-fold increase of melatonin content in response to high salt and drought treatment.…”
Section: Flavonoids and Other Phenolic Compoundsmentioning
confidence: 99%
“…Melatonin represents another stress-responsive metabolite involved in antioxidant defense in several Hypericum representatives, e.g., H. perforatum , or H. kouytchense ( Murch and Saxena, 2006 ; Nguyen et al., 2018 ; Chung and Deng, 2020 ; Khan et al., 2020 ). According to Zhou et al.…”
Section: Phenotyping Of Secondary Metabolism In Response To Biotic/ab...mentioning
confidence: 99%
“…Melatonin was first reported to have a daily rhythm in Chenopodium rubrum L. in 1997 (Kolar et al, 1997) and since has been found to show rhythmic (n = 13) and diurnal (n = 11) levels in: lupine (Lupinus albus L.; Hernandez-Ruiz and Arnao, 2008), water hyacinth (Eichhornia crassipes (Mart.) Solms; Tan et al, 2007a), sweet cherry (Zhao et al, 2013), eggplant (S. melongena; Korkmaz et al, 2017), rice (Wei et al, 2016), tomato (Arnao and Hernández-Ruiz, 2013), St. John's wort (Chung and Deng, 2020), and Arabidopsis (Li D. et al, 2020). Several melatonin metabolites have also been found to mimic melatonin expression patterns including 3-OHM (Choi and Back, 2019a) and AFMK (Tan et al, 2007a).…”
Section: Major Research Theme -Light Responsesmentioning
confidence: 99%